Efektivitas Pembelajaran Daring Masa Pandemi Covid-19 SMK Negeri 1 Beingin - Erli Mutiara; Nanda Dwi Gusnita; Esi Emilia; Adikariani Adikariani; Lelly Fridiarty (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
The research objectives are 1) Analyzing the effectiveness of online learning according to the experiences of students, teachers, and parents; 2) Knowing the learning outcomes of Indonesian Cake Products; 3) Analyzing the relationship between the effectiveness of online learning according to the student experience and learning outcomes of Indonesian Cake Products. The research location is at SMK Negeri 1 Beringin Deli Serdang, North Sumatra. The research time is November 2020-January 2021. The population is all students of class XI culinary, teachers who teach in class XI culinary, and parents of class XI culinary students. The sampling technique in total sampling amounted to 114 people. Data collection techniques used are tests and questionnaires. Data analysis by Descriptive data a and Spearman Rank test. Based on the result of research on the effectiveness of online learning according to the experiences of students, teachers, and parents, it is categorized as quite effective with scores of 86 percent, 71.43 percent, and 78 percent, respectively. The trend level of learning outcomes for Indonesian Cake Products is in the good category with a value of 84 percent. Based on the results of the spearman rank correlation analysis, there is a positive and significant relationship between the effectiveness of online learning based on student experience and the learning outcomes of Indonesian Cake products with a sig (p) = 0.00 <0.05 (r = 0.985) meaning the higher the effectiveness of online according to the student experience, the learning outcomes of Indonesian Cake Products are getting higher.